Alignment of liquid crystal E7 in composite photonic crystals based on single crystal silicon - PEROVA, TANIA (SPIE, 2005)
The orientation of nematic liquid crystal (LC) E7 on the surface of (111) silicon wafers and in the channels of grooved silicon structure has been investigated. Grooved Si is a periodical structure obtained by wet anisotropic etching of deep and narrow grooves in (110) Si using an alkaline solution. This structure can serve as a one-dimensional (1D) photonic crystal. Composite structures obtained from grooved Si infiltrated by LC are promising candidates for electro-optic application. LC E7 was infiltrated into the channels of grooved Si and into the bulk Si cells. IR spectroscopy and capacitance-voltage characteristics under DC electric field were applied to investigate LC orientation. It is shown that the E7 liquid crystal in grooved silicon exhibits a weak planar orientation with respect to the silicon walls.
Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
PUBLISHED
Dublin, Ireland
Keywords: 1D photonic crystals; Silicon; liquid crystals; infrared spectroscopy